Comprehensive Analysis of Potential Common Pathogenic Mechanisms for COVID-19 Infection and Gastric Cancer - Guiqian Zhang; Ning Wang; Shixun Ma; Yan Zhang; Pengxian Tao; Hui Cai (Analytical Cellular Pathology)
A growing body of data suggests that the prevalence of COVID-19 pneumonia in patients with stomach cancer is much higher than in the general population. However, these mechanisms are still not fully understood. After a thorough examination of shared differentially expressed genes (DEGs) for gastric cancer (GC) and COVID-19 pneumonia, we performed functional annotation, protein–protein interaction (PPI) networks, module design, and pivot gene identification. qPCR was used to verify the expression of hub genes in GC. Finally, a pivotal gene transcription factor-gene regulatory network was created and validated. According to functional enrichment analysis, common genes are mainly enriched in biological processes such as extracellular matrix tissue and extracellular structural tissue. Finally, five genes were found to be pivotal genes in the pathogenesis of GC and COVID-19 pneumonia: BGN (biglycan), UBE2C (ubiquitin-conjugating enzymes 2C), SPP1 (secreted phosphoprotein 1), THBS2 (thrombospondin 2), and COL1A1 (type I collagen alpha 1). These shared pathways and pivotal genes could provide new insights for more mechanistic studies.